The Effectiveness of Geography Learning and its Effect on Disaster Response at the State Senior High Schools in Padang City - Asep, Asep (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This research was aimed to describe and analyze the effectiveness of Geography learning at state senior high schools in Padang City and its effect on disaster response. The research method was Mixed Method. The data were collected through observation, interview and documentation. The analysis of the data suggested that the effectiveness of Geography learning at state high schools in Padang city was effective to very effective. It was influenced by teachers’ ability in opening the lesson and motivating the students, teachers’ strategies and supported media. Learning evaluation consisted of student’s knowledge evaluation ( written test and task), behavior evaluation (peer’s observation and self-assessment), and skill evaluation (Practice, Project, and Portfolio.) Students’ learning activity and response at state senior high schools in Padang City were categorized as effective to very effective. This was influenced by school social environment, student’s socio-economic factors and school physical environment. Regarding students’ learning mastery, it was found that schools located in the centre and the outskirt of the city obtained > 75 for individual learning mastery. Furthermore, for classical learning mastery, the schools in the downtown achieved 97.5% or more than 75 (completed). Meanwhile, the shools located in the outskirt had yet to score more than 75 or it only scored 74%. The cause was the difficulty in lesson planning, for example preparing media for learning. In addition, the difficulty was also affected by technlogical factors (smartphone) and student’s social environmental factors. Moreover, from the evaluation, it was found that the significant problem was time allocation for assessing the learning outcomes so it had an effect on disaster response in school, namely student’s readiness in receiving learning materials, teacher’s competence and the availability of learning facilities and infrastructures. Some prior policies regarding the effectiveness improvement are the use of learning media, the development of learning strategies, the development of learning model and method, improving learning facilities and supporting infrastructures as well as increasing teachers’ interest in participating in the forum of subject teachers (Musyawarah Guru Mata Pelajaran). Key words : Learning Effectiveness, Disaster Response, Geography Learning